ФОРМИРОВАНИЕ ПРОФЕССИОНАЛЬНОЙ КУЛЬТУРЫ СОВРЕМЕННОГО ЮРИСТА - Мохоров Дмитрий Анатольевич (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The multidimensionality of the characteristic features of the professional culture of a particular specialist in the field of jurisprudence is closely related to his effectiveness in protecting the rights of those legal entities and individuals whom he represents in legal relations in various areas of economic, social, and political life of society. In this connection, the author has made an attempt to analyze in detail the most important elements of the individual legal culture of lawyers in order to identify a set of legal competencies that determine the professional demand of legal workers as a real embodiment of their level of mastery of theoretical and practical skills.